Ophthalmic medical assisting : an independent study course - Stamper, Robert L (American Academy of Ophthalmology, 1991)
The textbook focuses on ophtalmology for ophthalmic medical assistants.
Keywords: Ophthalmic Assistants; Ophthalmology; oftalmologie; asistenti oftalmologů